Development of E-Achievements for Mapping Student Achievements in Vocational High Schools - Hidayat, Wahyu Nur; Pratama, Paskalis Edvin Aldo Krisrama (Universitas Negeri Malang, 2024)
This study focuses on the description, development, and determination of the feasibility level of a web-based management information system to assist in mapping students' achievements, talents, and interests. The benefits of developing a management information system can be felt from the perspective of students and schools, as it facilitates the management and mapping of achievements and helps schools improve accreditation. The development method used in this study refers to the 4-D development model, which has four stages: define, design, development, and deployment. The software testing results by software experts in terms of functionality showed a percentage of 100.00 per cent, and the media validation results showed a percentage of 90.00 per cent, with both criteria being very valid and feasible. The My Achievements website was implemented by 40 students from classes XI RPL 2 and XI TKJ 1 of SMKN 2 Singosari. User trial results showed a percentage of 82.20 per cent with good criteria. Meanwhile, the system usability scale test results showed a percentage of 84.70 per cent with good criteria. Based on the described data, it can be concluded that the My Achievements website has passed feasibility testing by software and media experts and is suitable for supporting the management, mapping of achievements, and dissemination of information for students at vocational high schools